Trade Unions and Life Satisfaction in Germany - Björn Becker; Laszlo Goerke; Yue Huang (British Journal of Industrial Relations, 2024)
The effects of trade union membership on wages and job satisfaction have been studied extensively. Arguably, life satisfaction serves as a more comprehensive measure of the benefits of union membership and warrants closer examination. Using all relevant waves from the German Socio-Economic Panel between 1985 and 2019, we find a negative correlation between trade union membership and life satisfaction in OLS and FE specifications. The association may arise because union members are more concerned about their job and the economic situation and less satisfied with their work. Social capital and wages also perform as channels between membership and life satisfaction. The negative correlation is more pronounced in settings in which trade unions are relatively~weak.
Keywords: 330; German socio-economic panel; industrial relations in Germany; life satisfaction; trade union membership